2004
DOI: 10.33549/physiolres.930448
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin – a pleiotropic molecule in acute and chronic inflammation.

Abstract: Calprotectin (MRP8/14, S100A8/S100A9, 27E10 antigen) is a heterodimer of two calcium-binding proteins present in the cytoplasm of neutrophils and expressed on the membrane of monocytes. Upon neutrophil activation or endothelial adhesion of monocytes, calprotectin is released and may be detected in serum or body fluids as potentially useful clinical inflammatory marker. The soluble form of calprotectin provides both bacteriostatic and cytokine-like effects in the local environment. When calprotectin metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(44 citation statements)
references
References 58 publications
1
41
0
2
Order By: Relevance
“…In line with our study, elevated calprotectin has been observed in neonatal infections, early stages of lung infection, early stages of heart and kidney transplant rejection, and in acute and chronic GVHD (graft versus host disease) in bone marrow transplant patients [33,34]. In 2017, Muhammet Fatih Topuz et al showed that serum calprotectin in patients with laryngeal cancer was significantly higher than in patients with benign laryngeal tumors, and evaluation of this protein as a diagnostic and prognostic biomarker was recommended [18].…”
Section: Plos Onesupporting
confidence: 91%
“…In line with our study, elevated calprotectin has been observed in neonatal infections, early stages of lung infection, early stages of heart and kidney transplant rejection, and in acute and chronic GVHD (graft versus host disease) in bone marrow transplant patients [33,34]. In 2017, Muhammet Fatih Topuz et al showed that serum calprotectin in patients with laryngeal cancer was significantly higher than in patients with benign laryngeal tumors, and evaluation of this protein as a diagnostic and prognostic biomarker was recommended [18].…”
Section: Plos Onesupporting
confidence: 91%
“…Additionally, the DAMP calprotectin, which is also known as the heterodimer of S100A8/A9, was studied as it accounts for up to half of the cytoplasmic protein content in neutrophils and is a well-established biomarker for several inflammatory diseases [ 63 , 64 , 65 , 66 ]. Calprotectin has diverse functions in the inflammatory response, including regulating inflammatory cell chemotaxis, adhesion, and activation [ 67 ]. At 3 h, clozapine caused significant increases in IL-1β levels in the spleen ( p < 0.01; Figure 7 B) and bone marrow ( p < 0.001; Figure 7 C) that were significantly dampened by PF-1355 pre-treatment ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Calprotectin belongs to the S100 family of calcium-binding cytosolic proteins normally present in regenerative cell types such as neutrophils, monocytes, macrophages, and endothelial and epithelial cells 1 . In neutrophils, monocytes, and activated macrophages, calprotectin constitutes 40% to 60% of the soluble cytosolic proteins, which suggests a specific function 1,2 .…”
mentioning
confidence: 99%